Barriers hindering tafakkur (thinking) from an Islamic perspective - Badi, Jamal Ahmed Bashier (2014)
Islam is a comprehensive and unique religion that captures all spheres of human endeavours. It does not only explain the creation of man but it captures the various concepts and compositions of man such as soul, hearth, thinking etc. Little attention of recent studies on Tafakkur explicitly elaborates on the vitality of barriers and hindrances that curtail Tafakkur. Therefore, the primary objective of this paper is to examine some implicit and explicit barriers that undoubtedly hinder Tafakkur from Islamic perspective. The methodology used in this paper is document analysis and it is as well a library-based research. The findings of this paper identified some barriers to Tafakkur such as: Jahl, Al-I’rāḍ, Taqlīd & Taʿṣṣub, Hawā. Hence, it recommends that, the identified predicaments to Tafakkur must be addressed through Islamic educational system, enlightenment and sensitization. It is hoped that if this is addressed, Tafakkur will be fruitful and positively utilized by Muslims in promoting various spheres of human endeavours in the Muslim world.